Overcoming Fat Shaming Through Self-Esteem In Vashti Harrison’s Big - Radiva Verve Waloyo (Faculty of Humanities, 2025)
This study examines how fat shaming and its impact as a social problem are represented in the picture book. This literature research also unveils the author‟s critical position toward the discourse. Fat shaming is a social issue in which individuals with a body size that is considered overweight or larger face discrimination. Criticizing someone‟s appearance becomes a social pressure, negatively affects the victim, and changes their perspective about their body. This problem can be seen in the picture book titled Big by Vashti Harrison (2023). In this study, the leading theory employed in conducting this research is the theory of representation by Stuart Hall (1997) and supported by the semiotic approach by Roland Barthes. There are also theories taken from several reputable journals to support the information about fat shaming, its impact, and self-esteem. This literary research is qualitative type of research because the data is in the form of words and images rather than numbers.
reupload 2026 Rudi H Validasi file repositori 8 Juni 2026_Dea_Firli
Keywords: Overcoming; Fat Shaming Through; Self-Esteem; Vashti Harrison’s Big